2017
DOI: 10.1038/s41598-017-05463-1
|View full text |Cite
|
Sign up to set email alerts
|

On the stochastic phase stability of Ti2AlC-Cr2AlC

Abstract: The quest towards expansion of the Mn+1AXn design space has been accelerated with the recent discovery of several solid solution and ordered phases involving at least two Mn+1AXn end members. Going beyond the nominal Mn+1AXn compounds enables not only fine tuning of existing properties but also entirely new functionality. This search, however, has been mostly done through painstaking experiments as knowledge of the phase stability of the relevant systems is rather scarce. In this work, we report the first atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
1
11
0
3
Order By: Relevance
“…] at elevated temperatures; here x is the stoichiometric weight of each element in the compound, ΔH form is the formation enthalpy; and ΔG SISSO is SISSO predicted entropic contribution to the ΔG form 21 . We note that the calculation of the finite-temperature phase stability of just one system may take millions of supercomputing CPU-hours, and months of actual calculation time, as demonstrated in work by a subset of these authors in the investigation of the phase stability in the Ti 2 AlC-Cr 2 AlC quaternary system 19 .…”
Section: Sisso Predicted δG Form Of Max Phasesmentioning
confidence: 98%
See 2 more Smart Citations
“…] at elevated temperatures; here x is the stoichiometric weight of each element in the compound, ΔH form is the formation enthalpy; and ΔG SISSO is SISSO predicted entropic contribution to the ΔG form 21 . We note that the calculation of the finite-temperature phase stability of just one system may take millions of supercomputing CPU-hours, and months of actual calculation time, as demonstrated in work by a subset of these authors in the investigation of the phase stability in the Ti 2 AlC-Cr 2 AlC quaternary system 19 .…”
Section: Sisso Predicted δG Form Of Max Phasesmentioning
confidence: 98%
“…Fortunately, it has been demonstrated that DFT calculations augmented with machine learning and experimentally acquired information provides the means for predicting material properties quickly and accurately 21 . The SISSO framework, for example, is an emerging machine-learning algorithm capable of arriving at accurate predictions of material properties through models that employ physically meaningful features [17][18][19] . Here, we utilize the descriptor-based model from Bartel for the finite-temperature Gibbs energy of an arbitrary inorganic stoichiometric phase 21 :…”
Section: Sure Independence Screening and Sparsifying Operatormentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the CALPHAD community has begun to address some of these issues. In 2017, Duong et al constructed Bayesian CALPHAD models for multicomponent M AX nanolaminate materials [14]. In that work, they assessed the relative probability of stability of a number of phases by drawing samples from the CALPHAD parameter distributions and a range of composition at a specified temperature.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…As a consequence, in a number of previous studies the Al Cr phase has been omitted from the refinement due to the lack of crystal structure data (see e.g. [23]). To obtain a fit, a model of the Al Cr unit cell had to be constructed based on published atom coordinates [22].…”
Section: Xrd Measurementsmentioning
confidence: 99%